L’histoire de l’éducation au sein des sciences de l’éducation : un champ de recherche passerelle ? - Sylvain Wagnon (Éducation et Socialisation)
The history of education is a field of research, but it is also a possible bridge between history and the sciences of education. How to conceive a history of education at once a historical research discipline and an auxiliary science of pedagogical action ? The history of education is for us a place to the emergence of approaches that combines historical rigor and praxeological approach. It is a privileged place to articulate the interactions between the past and the present. From this methodological positions, we would like to perceive, some caracteristics of the history of education, before proposing an opening towards the material history of education.